CAR-T Cells: Precision Cancer Immunotherapy - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Current cancer drugs and treatments are aiming at eradicating tumor cells, but often are more toxic then effective, killing also the normal cells and not selectively the tumor cells. There is good personalized cancer therapy that involves administration to the cancer-bearing host of immune cells with direct anticancer activity, which called adoptive cell therapy (ACT). A review of the unique biology of T cell therapy and of recent clinical experience compels a reassessment of target antigens that traditionally have been viewed from the perspective of weaker immunotherapeutic modalities.CONTENT: Chimeric antigen receptors (CAR) are recombinant receptors which provide both antigen-binding and T cell-activating functions. Many kind of CARs has been reported for the past few years, targeting an array of cell surface tumor antigens. Their biologic functions have extremely changed following the introduction of tripartite receptors comprising a costimulatory domain, termed second-generation CARs. The combination of CARs with costimulatory ligands, chimeric costimulatory receptors, or cytokines can be done to further enhance T cell potency, specificity and safety. CARs reflects a new class of drugs with exciting potential for cancer immunotherapy.SUMMARY: CAR-T cells have been arising as a new modality for cancer immunotherapy because of their potent efficacy against terminal cancers. They are known to exert higher efficacy than monoclonal antibodies and antibodydrug conjugates, and act via mechanisms distinct from T cell receptor-engineered T cells. These cells are constructed by transducing genes encoding fusion proteins of cancer antigen-recognizing single-chain Fv linked to intracellular signaling domains of T cell receptors.KEYWORDS: chimeric antigen receptor, CAR-T cells, adoptive cell therapy, ACT, T cell receptor, TCR, cancer, immunotherapy